Levantamento de coeficientes de desempenho de refrigeradores domésticos associados a armazenador térmico - Marchi Neto, Ismael de [UNESP] (2007)
Due to the extreme necessity to diversify renewable energy sources, the search for energy recycling methods through the utilization of thermal losses from equipment has become fundamental. Thus, these losses can be used as new source of energy for water heating and storage in Domestic Hot Water Storage Tanks (DHWST). For this reason, the construction of an experimental apparatus with a cylindrical thermal storage tank is proposed, in which the objective of the study will be a survey of the Coefficient of Performance concerning conventional and modified refrigerators, as well as to perform an analysis of hot water, through the thermal stratification technique using a refrigerator with a modified condenser. The collected thermal loss, as per the thermosiphon principle, will be stored as thermal energy. The results showed that the coefficient of performance for the systems, calculated using techniques for theoretical and experimental thermal losses, presented great differences. The dynamic behavior of the thermal distribution was observed through the thermal stratification effect and temperature evolution in terms of time, showing greater variability of the modified refrigerator generating more thermal comfort to users in addition to providing domestic hot water.